Potential Vector Shelter for Malaria in South Central Timor Regency in Indonesia (Majalah Kedokteran Bandung, 2020)
More than half of the areas in East Nusa Tenggara province, a province in the eastern part of Indonesia, are planned to be free from malaria by the end of 2030. However, one of the critical indicators for malaria elimination is still lacking, i.e. vectors’ environment and  breeding place indicators. South Central Timor (SCT) District is one of the areas with the highest Annual Parasite Incidence (API) >2â€° with the majority of the population works as farmers. The purpose of this study was to capture the relationship between environmental factors and the prevalence of malaria. This study was a cross-sectional analytic retrospective study using data from a previous malaria study conducted in August 2013 to September 2014 in 5 sub-districts of SCT district. All respondents were selected using the systematic random sampling approach from the population of healthy people. Data were collected using a standard questionnaire and an observation environment form. Malaria was confirmed through microscopic and Polymerase Chain Reaction (PCR) examinations. Data were then analyzed using the bivariate and multivariate analysis with 95% CI and Î±:0.05. Of 357 data collected, 35% (125/357) were malaria positive based on PCR examination. Two variables (living nearby lagoon and nearby rice field) were significant (p-value
Keywords: Malaria prevalence; South Central Timor Regency; Vector shelter